Analgesia after total knee replacement: local infiltration versus epidural combined with a femoral nerve blockade. A prospective, randomised pragmatic trial - YaDeau, Jacques T. (2013)
In a randomised controlled pragmatic trial we investigated whether local infiltration analgesia would result in earlier readiness for discharge from hospital after total knee replacement (TKR) than patient-controlled epidural analgesia (PCEA) plus femoral nerve block. A total of 45 patients with a mean age of 65 years (49 to 81) received a local infiltration with a peri-articular injection of bupivacaine, morphine, and methylprednisolone, as well as adjuvant analgesics. In 45 PCEA+femoral nerve blockade patients with a mean age of 67 years (50 to 84), analgesia included a bupivacaine nerve block, bupivacaine/hydromorphone PCEA, and adjuvant analgesics. The mean time until ready for discharge was 3.2 days (1 to 14) in the local infiltration group and 3.2 days (1.8 to 7.0) in the PCEA+femoral nerve blockade group. The mean pain scores for patients receiving local infiltration were higher when walking (p = 0.0084), but there were no statistically significant differences at rest. The mean opioid consumption was higher in those receiving local infiltration. The choice between these two analgesic pathways should not be made on the basis of time to discharge after surgery. Most secondary outcomes were similar, but PCEA+femoral nerve blockade patients had lower pain scores when walking and during continuous passive movement. If PCEA+femoral nerve blockade is not readily available, local infiltration provides similar length of stay and similar pain scores at rest following TKR.